1990
DOI: 10.1557/jmr.1990.2933
|View full text |Cite
|
Sign up to set email alerts
|

Refractory semiconductor of boron phosphide

Abstract: The single crystal growth of boron phosphide (BP) by employing the high pressure flux method and chemical vapor deposition (CVD) process is described together with characterization of the prepared BP and its electrical, thermal, semiconducting, and electrochemical properties. BP single crystals prepared by the high pressure flux method contain copper used as the flux, but they are promising for photocathode materials. BP single crystalline wafers prepared by the CVD process using Si wafer substrate contained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
66
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…(3), however, some additional hightemperature C p (T) data are required. Unfortunately, one is concerned in thermo-chemical literature, particularly for BP, with rather large uncertainties between C p (T) values published by different authors [56,57] (as shown by differences up to an order of 4 J K À1 mol À1 , in the region (7) and (8)). …”
Section: Iii-v Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3), however, some additional hightemperature C p (T) data are required. Unfortunately, one is concerned in thermo-chemical literature, particularly for BP, with rather large uncertainties between C p (T) values published by different authors [56,57] (as shown by differences up to an order of 4 J K À1 mol À1 , in the region (7) and (8)). …”
Section: Iii-v Materialsmentioning
confidence: 99%
“…3). Nevertheless, it turned out to be possible of estimating, at least roughly, the general trend of a monotonic increase of the C p (T) curve for BP up to about 800 K. To this end we have performed a simultaneous least-mean-square fit of the relatively accurate low-temperature data set [55] in combination with the largely uncertain high-temperature data sets [56,57] (the latter having been included with significantly lower weights; see further remarks on this point in the Appendix D). In this way we have obtained for BP the approximate parameter set given in Table 1.…”
Section: Iii-v Materialsmentioning
confidence: 99%
“…The cell was pressure-calibrated at room temperature using phase transitions in Bi (2.55 and 7.7 GPa), PbSe (4.2 GPa), and PbTe (5.2 GPa). The temperature calibration under pressure was made using well-established reference points: melting of Si, NaCl, CsCl, Pt, Rh, Al 2 …”
mentioning
confidence: 99%
“…The boron monophosphide is well known as a refractory semiconductors (1,2), but the rhombohedral boron phosphide is a wide-gap (3.3 eV) semiconductor (3).…”
Section: Introductionmentioning
confidence: 99%